2022
DOI: 10.7759/cureus.31988
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Tip Position of Central Venous Catheters Inserted Using Peres’ Height Formula

Abstract: Objectives: The tip of a central venous catheter (CVC) should be positioned in the proximity of the cavoatrial junction (CAJ) where the lower third of the superior vena cava (SVC) and the upper right atrium (RA) are located to prevent life-threatening complications. This study aimed to determine the accuracy of Peres' height formula in predicting the correct insertion depth of CVC.Methods: A total of 332 patients were enrolled in this prospective observational study. All CVCs were inserted using Peres' formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is thought that the difference in correct position of catheter tip, even though assuming the same formula, might be from that the method for identifying the optimal zone is different. We used TEE to confirm the ideal location of the catheter tip, whereas the authors used the carina on chest X-ray in the previous study [28]. We thought our study had a benefit in terms of the method to identify the SVC-RA junction and the optimal point for catheter tip placement, which was defined in the present study, because of the type of surgery requiring intraoperative TEE.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is thought that the difference in correct position of catheter tip, even though assuming the same formula, might be from that the method for identifying the optimal zone is different. We used TEE to confirm the ideal location of the catheter tip, whereas the authors used the carina on chest X-ray in the previous study [28]. We thought our study had a benefit in terms of the method to identify the SVC-RA junction and the optimal point for catheter tip placement, which was defined in the present study, because of the type of surgery requiring intraoperative TEE.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Şahinkaya et al conducted a study to reexamine Peres' formula [28]. The authors reported that when using the Peres' formula, the correct position of the catheter tip was reached in 84.7% (133/157) of cases using the right internal jugular vein as a route for central venous catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Still, the Peres equation [ 7 ] has been shown to have a lower performance in female and obese Turkish individuals. [ 6 ] Struck et al [ 21 ] showed that the Peres and Czepizak formulas performed adequately for individuals 170–180 cm tall but less well in smaller or taller individuals. In addition, those formulas have a 48%-94.5% correct placement rate.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, regardless of the chosen approach, it is essential to ensure that the tip of the catheter does not exceed the junction of the superior vena cava and the right atrium, making accurate preoperative estimation crucial. [3][4][5][6] Accurate catheter length estimation is expected to avoid the psychological impact on patient and infection risks secondary to catheter adjustment, especially for infusion ports.…”
Section: Introductionmentioning
confidence: 99%
“…In the current case, we suggest that emphysematous thrombophlebitis may be attributed to emergency surgery, absence of anticoagulant use, insertion without ultrasound assistance, and misplacement of the CVC tip from the right subcalvian vein into the IJV[ 4 , 12 ]. The term ‘misplacement’ refers to migration of the CVC tip to an improper position[ 13 ].It is recommended that the CVC tip be positioned at the junction of the SVC and right atrium[ 14 ], a location with high blood flow to reduce the risk of thrombosis but still lying outside the atrium, thereby preventing arrhythmia[ 15 ]. In the current case, the tip of the CVC was implanted via subclavian vein access towards the head rather than caudally toward the junction of the SVC and right atrium.…”
Section: Discussionmentioning
confidence: 99%